Angular Crash Course - Thippireddy, Bharath (Packt Publishing, 2019)
Master Angular and create a Single Page App using Angular, Node, Java, and Express in simple steps About This Video Explore what single-page applications (SPAs) are Understand how Angular makes it easy to build SPAs Get to grips with Angular while building a single-page application using Java, Node.js, and Express In Detail Angular.js is one of the most widely used single-page application development frameworks in the industry. It makes it easier than ever to create efficient and production-ready single-page applications. In this course, you will learn how to create REST APIs using Express and Java Spring Boot. You will even use them in your Angular frontend and build full stack applications from scratch. The course will also guide you through creating Angular components. As you advance, you'll get to grips with developing and using pipes to format data effectively. The course will later take you through creating custom directives and using them. Toward the concluding sections, you'll learn how to build a check-in app to check-in passengers. By the end of this course, you'll have explored the essential Angular features and have gained the skills you need to build robust single-page applications.